Comparison of immunoturbidimetric and Lowry methods for measuring concentration of very low density lipoprotein apolipoprotein B-100 in plasma. Issue 2 (February 1994) - Cummings, M H; Watts, G F; Lumb, P J; Slavin, B M
Abstract : To assess whether the Lowry-tetramethylurea method for measuring apolipoprotein B-100 (apo-B) in very low density lipoprotein (VLDL) could be replaced by direct assay of VLDL apo-B using a highly practicable immunological method. Seventy five fasting blood samples were collected from patients attending the lipid clinic at this hospital. Plasma was separated immediately and VLDL isolated by preparative ultracentrifugation at solution density 0.93-1.006 kg/l. Apo-B was precipitated from an aliquot of the VLDL fraction using the tetramethylurea (TMU) technique and protein mass determined by the Lowry method (LM); mean apo-B 83.02 micrograms/ml (SD 74.85). Apo-B was also measured in VLDL using direct immunoturbidimetry on the Cobas-Fara analyser; mean apo-B 82.32 micrograms/ml (SD 72.88). There was a very close correlation between methods (immunoturbidimetry = 0.94.LM + 3.95, r = 0.97, p < 0.001). The mean difference between methods (constant error) was small (0.70 microgram/ml) and not significant (p = 0.742). Random error was 13.01 micrograms/ml by analysis of variance. It is concluded that immunoturbidimetry, a more rapid and convenient test, may replace the LM and TMU techniques for measuring VLDL apo-B concentration and that this method could be applied to research studies requiring analysis of large numbers of samples.